(untitled) (Comparatismi, 2025)
This essay examines the authorial strategies employed by Milan Kundera to influence the reception and legitimation of his work between France and Czechoslovakia, within the broader context of the progressive globalization of the literary field. Focusing on the editorial and critical success of The Unbearable Lightness of Being (1984), the analysis highlights the tension between the construction of a supranational authorial image and the identity constraints imposed by both the publishing market and literary criticism, Western and Czech alike. Central to the discussion are the notions of authenticity, alterity, and canon, reconsidered in light of the transformations of migrant authorship and the mechanisms of selective inclusion enacted by the French publishing system. The case of Kundera thus emerges as a paradigm of liminal authorship, navigating between the need for aesthetic self-assertion and the symbolic pressures of external legitimating structures.